Factors and conditions of the environmental and economic security formation in Ukraine - Britchenko, Igor; Drotarova, Jozefina; Yudenko, Oksana; Holovina, Larysa; Shmatkovska, Tetiana (My University, 2022)
The article examines the peculiarities of the formation of the ecological and economic security system and the specifics of its principles. The relevance of the transformation of approaches to understanding the essence and principles of ecological and economic security in the context of the need to ensure sustainable development is substantiated. The levels of ecological and economic security and the peculiarities of changes in profits and costs during the transition of the economic system and business entities between these levels are determined. The principles of implementation and formation of economic tools for ensuring environmental safety are proposed.
Keywords: Ecological and economic security; Ecosystem approach; Ecological management; Levels of ecological security